Factors associated with current posttraumatic stress disorder among COVID-19 vaccinated older adults in Israel. (October 2021) - Palgi, Yuval; Greenblatt-Kimron, Lee; Hoffman, Yaakov; Goodwin, Robin; Ben-Ezra, Menachem
Abstract: This is the first study to examine COVID-19 vaccine-related stressors in the context of current posttraumatic stress disorder (PTSD) symptoms amongst older adults exposed to traumatic events prior to the COVID-19 outbreak, with particular focus on the associations between ageism, vaccine-related stressors and PTSD. Five hundred and sixty-three participants aged 65 and above reported exposure to at least one traumatic event, their current PTSD level, physical and mental health, ageist attitudes, and vaccine related stressors. Univariate logistic regression revealed that depressive symptoms, ageism, vaccine hesitancy and severity of side effects were the main factors associated with clinical levels of current PTSD. These results suggest that older adults were vulnerable to intensified PTSD symptoms, not only as a result of greater depression, but also as a consequence of other factors, including ageism, vaccination hesitancy and vaccination side effects. Practitioners would benefit from awareness to these factors.